INTERNALISASI NILAI AKHLAK MELALUI MANAJEMEN SARANA DIGITAL DALAM MENGHADAPI TANTANGAN PERILAKU DIGITAL DI MA TARBIYATUL IHSAN KECAMATAN SUMBERASIH - Dafa Ihsa Mahendra; aisyah aqila; Wardatul Jannah; Abdul Karim; Devy Habibi Muhammad (As-Sulthan Journal of Education, 2026)
This study aims to analyze the internalization of moral values and the management of digital facilities at MA Tarbiyatul Ihsan in responding to educational challenges in the digital era. The research employed a qualitative approach with a case study design. Participants were selected through purposive sampling, involving the principal, teachers, and students. Data were collected through observation, interviews, and documentation. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that MA Tarbiyatul Ihsan has integrated various digital facilities into the learning process, including projectors, computer laboratories, and internet networks, although technical constraints such as limited electrical capacity remain a challenge. The internalization of moral values is implemented through habituation programs, teacher role modeling, school regulations, and character-building activities integrated into the learning process. The main challenge identified is students' digital distraction, particularly the inappropriate use of mobile phones during learning activities. To address this issue, teachers employ supervision, persuasive approaches, digital ethics education, and a point-based disciplinary system. The study concludes that the successful internalization of moral values in the digital era requires synergy between effective digital facility management, teacher role modeling, and continuous character habituation. These findings contribute to the development of Islamic education models that integrate technological advancement with moral value reinforcement.